Braudel´s model of historical structures and interpretative significance to teach church history in the Slovak school system - PaedD, ThLic.; Genčúrová, Gabriela (IJRDO- Journal of Educational Research, 2016)
This thesis presents the theory of temporalities of F. Braudel as method of new interpretationof historical time. It also pplies a new interpretation of historical time of space and events tothe reading History of Church within the subject relegious education. Within the meaning ofBraudel model structuring of time and events in history it demonstrates the possibilities of anew way of interpretation church-historical subject matter. Braudel´s modification oftructuring time for educational purposes proves by concrete proposal of interactive didactictool called timeline „Longue durée“ as well as it supports application of Braudel´s oftemporalities into the teaching of Relegious education.